Therapeutic time window for the effects of erythropoietin on astrogliosis and neurite outgrowth in an in vitro model of spinal cord injury. Issue 9 (March 2018) - Hong, Hea Nam; Shim, Ju Hee; Won, You Jin; Yoo, Jong Yoon; Hwang, Chang Ho
Abstract: Background: The objective of this study was to investigate the underlying molecular mechanisms and the therapeutic time window for preventing astrogliosis with erythropoietin (EPO) treatment after in vitro modeled spinal cord injury (SCI). Methods: Cultured rat spinal cord astrocytes were treated with kainate and scratching to generate an in vitro model of SCI. EPO (100U/mL or 300U/mL) was added immediately or 2, 4, or 8 hours after injury. Some cultures were also treated with AG490, an inhibitor of the EPO-EPO receptor (EpoR) pathway mediator Janus kinase 2 (JAK2). To evaluate neurite extension, rat embryonic spinal cord neurons were seeded onto astrocyte cultures and treated with EPO immediately after injury in the presence or absence of anti-EpoR antibody. Results: EPO treatment at up to 8 hours after injury reduced the expression of axonal growth inhibiting molecules (glial fibrillary acidic protein, vimentin, and chondroitin sulfate proteoglycan), cytoskeletal regulatory proteins (Rho-associated protein kinase and ephephrin A4), and proinflammatory cytokines (tumor necrosis factor-alpha, transforming growth factor-beta, and phosphorylated-Smad3) in a dosedependent manner ( P < .001). Most effects peaked with EPO treatment 2–4hours after injury. Additionally, EPO treatment up to 4 hours after injury promoted expression of the EpoR (>2-fold) and JAK2 (>3-fold) in a dose-dependent manner ( P < .001), whereas co-treatment with AG490 precluded these effects ( P < .001). EPO treatment up to 4hours after injury also enhanced axonal b-III tubulin-immunoreactivity (>12-fold), and this effect was precluded by co-treatment with an anti-EpoR antibody ( P < .001). Conclusions: EPO treatment within 8 hours after injury reduced astrogliosis, and EPO treatment within 4 hours promoted neurite outgrowth. EPO therapy immediately after spinal cord injury may regulate glia to generate an environment permissive of axonal regeneration.